Enhanced carbon export to the abyssal depths driven by atmosphere dynamics. Issue 16 (25th August 2016) - Pedrosa‐Pàmies, R.; Sanchez‐Vidal, A.; Canals, M.; Lampadariou, N.; Velaoras, D.; Gogou, A.; Parinos, C.; Calafat, A.
Abstract: Long‐term biogeochemical observations are critical to understand the natural ability of the oceans to fix CO2 into organic carbon and export it to the deep as sinking particles. Here we present results from a 3 year (2010–2013) sediment trap deployment that allowed detecting interannual variations of carbon fluxes beyond 4000 m depth in the Eastern Mediterranean Sea. Anomalous atmospheric conditions triggering strong heat losses in winter–spring 2012 resulted in convective mixing, nutrient uplifting, and a diatom‐dominated bloom southeast of Crete. Phytoplankton growth, reinforced by the arrival of nutrients from airborne Etna volcano ash, was the highest in the last decade (satellite‐derived Chl a concentrations up to 1.9 mg m −3 ). This situation caused carbon export to increase by 2 orders of magnitude (12.2 mg m −2  d −1 ) with respect to typical values, which demonstrates how pulses of sinking fresh phytodetritus linked to rare atmospheric processes can episodically impact one of the most oligotrophic environments in the world ocean. Key Points: Atmosphere‐driven events enhance carbon export to the deep‐water oligotrophic environments Organic carbon fluxes at deep bathypelagic depth may increase 14‐fold during short‐lived events